Bioremediation in Upstream Oil and Gas Enterprises: Indonesian Environmental Law Perspectives - Rayhan, Ahmad; Ramadhan, Mahendra Utama Cahya; Sihotang, Tigor Boris Yudha Prakasa (Unifikasi : Jurnal Ilmu Hukum, 2023)
There have been changes in environmental management since the enactment of Law Number 11 of 2020 on Job Creation, particularly in bioremediation—upstream oil and gas enterprises. It is intriguing since the process includes a natural way of cleansing tainted oil in the water without harming the ecosystem. The study aims to examine the implementation of bioremediation in upstream oil and gas activities under Indonesian environmental law. The study also employed a normative juridical or doctrinal approach. According to the findings, bioremediation is being carried out under a profit-sharing contract with SKK Migas (Special Working Unit for Upstream Oil and Natural Gas Business Activities) acting as the implementing agency. The legal relationship position of an oil and natural gas mining company, specifically in bioremediation, is in the government and corporate accountability to carry out the program, referring to production-sharing contracts—cooperation contracts and applicable statutory provisions. To summarise, all parties, including national and regional governments, communities, and oil and gas companies, must implement ecologically friendly protection such as bioremediation.